V.O2peak, myocardial Hypertrophy, and Myocardial Blood Flow in endurance-trained men - Laaksonen, M. S.; Heinonen, I.; Luotolahti, M.; Knuuti, J.; Kalliokoski, K. K. (Medicine & Science in Sports & Exercise, 2014)
Introduction: Endurance training induces cardiovascular and metabolic adaptations, leading to enhanced endurance capacity and exercise performance. Previous human studies have shown contradictory results in functional myocardial vascular adaptations to exercise training, and we hypothesized that this may be related to different degrees of hypertrophy in the trained heart. Methods: We studied the interrelationships between peak aerobic power (V·O2peak), myocardial blood flow (MBF) at rest and during adenosine-induced vasodilation, and parameters of myocardial hypertrophy in endurance-trained (ET, n = 31) and untrained (n = 17) subjects. MBF and myocardial hypertrophy were studied using positron emission tomography and echocardiography, respectively. Results: Both V·O2peak (P < 0.001) and left ventricular (LV) mass index (P < 0.001) were higher in the ET group. Basal MBF was similar between the groups. MBF during adenosine was significantly lower in the ET group (2.88 ± 1.01 vs 3.64 ± 1.11 mL/g·min, P < 0.05) but not when the difference in LV mass was taken into account. V·O2peak correlated negatively with adenosine-stimulated MBF, but when LV mass was taken into account as a partial correlate, this correlation disappeared. Conclusions: The present results show that increased LV mass in ET subjects explains the reduced hyperemic myocardial perfusion in this subject population and suggests that excessive LV hypertrophy has negative effect on cardiac blood flow capacity.